Store‐operated calcium entry mediates hyperalgesic responses during neuropathy - Wei Wang; Qiru Wang; Jinlu Huang; Hong Li; Fangjie Li; Xue Li; Ruimei Liu; Ming Xu; Jinghong Chen; Yemeng Mao; Le Ma (FEBS Open Bio, 2023)
Neuropathic pain (NP), resulting from nerve injury, alters neural plasticity in spinal cord and brain via the release of inflammatory mediators. The remodeling of store‐operated calcium entry (SOCE) involves the refilling of calcium in the endoplasmic reticulum via STIM1 and Orai1 proteins and is crucial for maintaining neural plasticity and neurotransmitter release. The mechanism underlying SOCE‐mediated NP remains largely unknown. In this study, we found SOCE‐mediated calcium refilling was significantly higher during neuropathic pain, and the major component Orai1 was specifically co‐localized with neuronal markers. Intrathecal injection of SOCE antagonist SKF96365 remarkably alleviated nerve injury‐ and formalin‐induced pain and suppressed c‐Fos expression in response to innocuous mechanical stimulation. RNA sequencing revealed that SKF96365 altered the expression of spinal transcription factors, including Fos, Junb, and Socs3, during neuropathic pain. In order to identify the genes critical for SKF96365‐induced effects, we performed weighted gene co‐expression network analysis (WGCNA) to identify the genes most correlated with paw withdrawal latency phenotypes. Of the 16 modules, MEsalmon module was the most highly correlated with SKF96365 induced effects. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that the enriched genes of MEsalmon module were significantly related to Toll‐like receptor signaling, steroid biosynthesis, and chemokine signaling, which may mediate the analgesic effect caused by SKF9636 treatment. Additionally, the SOCE antagonist YM‐58483 produced similar analgesic effects in nerve injury‐ and formalin‐induced pain. Our results suggest that manipulation of spinal SOCE signaling might be a promising target for pain relief by regulating neurotransmitter production and spinal transcription factor expression.